Identificação precoce do risco para transtornos da atenção e da leitura em sala de aula - Andrade, Olga Valéria [UNESP]; Andrade, Paulo Estêvão [UNESP]; Capellini, Simone Aparecida [UNESP] (FapUNIFESP (SciELO), 2013)
In this his study the accuracy was investigated of collective pedagogical activities, based on phonological judgments by matching figures and figures to spoken words, to identify students at risk for reading and/or attention disorders. Forty-five second graders (mean age of 7 years, 29 males) were divided into two groups, a control group, without reading difficulties (n=32), and an at-risk group, with reading difficulties (n=13). The low-achievement on these collective activities, defined by scores more than 1.65 SD below the mean of the control group, presented good sensitivity (true positives) and specificity (true negatives) in the early identification of at risk students.
Early identification of attention and reading disorders in the classroom
Keywords: Dyslexia; Education; Learning disorders